Perinatal Morbidity & Mortality following repeat Cesarean section due to five or more previous Cesarean Section done in Tertiary centre in KSA - Osman, Somia; Farid, Gehan; Kamal, Reem Mohamed; Ali, Sarah Rabie; Swaraldahab, Mohamed AH (Clinical Journal of Obstetrics and Gynecology, 2018)
Objectives: To highlight and determine the maternal and neonatal outcome and associated risks for patients who have undergone their 6th and more caesarean sections. Design: Case control study. Setting: Tertiary Centre (Security Forces Hospital – Riyadh – Saudi Arabia). Patients: 80 patients selected to study group who have undergone their sixth and more caesarean sections in Security Forces Hospital. Between June 2006 and May 2010. This group was compared to 80 patients who have undergone their third to fifth caesarean sections during the same time period and immediately following the studied case. Main outcome measured:: Age and parity of women in study and the control group were correlated with the number of previous caesarean sections. Intra operative and post-operative maternal complications including presence and grade of adhesions, intra partum and postpartum hemorrhage, use of measurement and methods (both medical and surgical) to control bleeding such as Bakry balloon, Internal iliac artery ligation, etc., were highlighted. Bowel injury, blood transfusion, admission to surgical intensive care, incidence of placenta previa and accreta, post-operative complications like paralytic ileus, wound infection were also noted. Further, neonatal outcome including birth weight, Apgar score, and need for neonatal intensive care unit admission were reviewed. Results: Patients in the study group had higher incidence of extensive adhesions (41.25%) compared to (12.25%) in the control group. Bowel injury was (2.5%) in study group with none in the control group. The incidence of placenta previa was (8.75%) in the study group as compared to (2.5%) in the control group, with placenta accreta complicating (28.57%) of placenta previa seen only in the study group. Blood transfusion was higher in the study group (20%) as compared to (5%) in the control group. Neonatal admission to NICU was higher in the study group (27.5%) in comparison to the control group (12.5%). Also birth weight was lower in the study group. Conclusion: The more the number of caesarean sections, the more the maternal and neonatal morbidity. Patients should have proper counselling during antenatal follow up about the risks of repeated caesarean sections, and offered bilateral tubal ligation after the third or fourth caesarean sections.